Mechanism of Ca-Ba diffusion in lead-free (Ba, Ca)TiO3 piezoelectrics. Issue 1782 (2015) - Shu, Chang; Reed, Daniel; Button, Tim
Abstract: The reaction mechanism of BaCO3 +CaCO3 +TiO2 by solid state methods has been studied in this work using thermal analysis (DSC-TG) from 500 to 1500 °C and in situ X-ray diffraction (XRD) from room temperature to 800 °C. In the mixed powders, the CaO is firstly formed followed by presence of an intermediate Ba2 TiO4 phase and finally the formation of CaTiO3, BaTiO3 and/or (Ba, Ca)TiO3, where the presence of CaO or CaTiO3 (CT) has slowed down the formation of BaTiO3 (BT). Raman microscopy of a BT-CT diffusion couple has shown that Ca 2+ firstly diffuses into the BT grain boundaries and then into the BT core.